Ar (λ)-weighted Caccioppoli-type and Poincaré-type inequalities for A-harmonic tensors - Bing Liu (International Journal of Mathematics and Mathematical Sciences)
We prove a local version of weighted Caccioppoli-type inequality, then we prove a version of weighted Poincaré-type inequality for A-harmonic tensors both locally and globally.